Learning about fiscal multipliers during the European sovereign debt crisis: Evidence from a quasi-natural experiment - Lucyna Górnicka; Christophe Kamps; Gerrit Koester; Nadine Leiner-Killinger (European Central Bank (ECB), 2018)
Identifying fiscal multipliers is usually constrained by the absence of a counterfactual scenario. Our new data set allows overcoming this problem by making use of the fact that recommendations under the EU's excessive deficit procedure (EDP) provide both a baseline no-policy-change scenario and a fiscal-adjustment EDP scenario that entails a forecast of the macroeconomic impact of fiscal consolidation over the EDP horizon. For a sample of 24 EU countries to which 48 EDP recommendations were applied between 2009 and 2015, we derive country-specific fiscal multipliers as actually applied by forecasters during the crisis. Our results confirm Blanchard and Leigh's (2013, 2014) presumption that forecasters learned during the crisis. According to our findings, fiscal multipliers as applied by the European Commission increased over time - from about 1/4 in the early years of the crisis to about 2/3 in the later years. However, different from Blanchard and Leigh (2013, 2014), we do not find evidence for the hypothesis that ex-post fiscal multipliers have been substantially above 1 during the crisis.
Keywords: E32; E62; H20; H5; 330; fiscal consolidation; fiscal multipliers; business cycle